APPLICATION SETTINGS parking lot and retribution IN CARS WITH CARDS storey building electrical - Eriek Orlando (Majalah SIKOMTEK, 2010)
Number of companies and shopping centers that have employees or visitors in a very large amount of parking needed large enough to put their fleet. Prototype system for managing parking lot parking lot has been realized, the system is using Borland Delphi 5 application as an application fee and application programming BASCOM as to set the microcontroller AT89S52 as controller hardware. With this system, can help the building managers in managing parkirannya to be more organized and make profit, karenakan not require too much staff and the accuracy of counting the cost of parking. In addition, users also get the convenience of parking their vehicles in place and not feel harmed would be parking fees that are not in accordance with a predetermined.